Enhancing Students’ Understanding of Islamic Civilization through Technology-Integrated Learning Models at MTS NW Bual: A Classroom Action Research - Sudiati; Yardi Rahman (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This Classroom Action Research (CAR) aims to explore the effectiveness of technology-integrated learning models in enhancing students’ understanding of Islamic Civilization (Sejarah Kebudayaan Islam or SKI) at MTS NW Bual. The study involves eighth-grade students, where technology-based tools and resources, such as digital presentations, interactive apps, and online research, are incorporated into the SKI curriculum. The primary goal is to determine whether these technological interventions can improve students’ engagement, understanding, and retention of historical and cultural content related to Islam’s history and civilization. The research is implemented in two cycles, following the model of planning, action, observation, and reflection. In each cycle, teachers introduce various digital resources, including multimedia presentations, virtual tours, and collaborative online platforms, to facilitate learning about Islamic civilization. Data are collected through student assessments, observations, and feedback from both teachers and students to evaluate the impact of the technology-enhanced learning experience. The findings indicate that the integration of technology into SKI lessons significantly improved student engagement, comprehension, and the ability to relate historical concepts to contemporary contexts. Students showed greater enthusiasm and participation, particularly when using interactive tools that allowed them to explore Islamic history in more dynamic ways. Additionally, the technology-driven approach helped students retain information more effectively compared to traditional teaching methods. This research highlights the potential of using technology in Islamic history education, suggesting that such methods not only increase student engagement but also enhance learning outcomes. It is recommended that MTS NW Bual and similar institutions continue to incorporate technology in the classroom to foster more engaging, meaningful, and effective learning environments.